Survey on home loan refinancing in Singapore - Ang, Jasmine Qiao Wei (2008)
This report examines the considerations of home loan borrowers and their knowledge on refinancing opportunities of home loans. The lack of research regarding refinancing and the increasing home loan rates due to the rising SIBOR motivated us to explore this topic. We discuss implications of our findings and make specific recommendations applicable for banks, online portals and consumers accordingly. Our major recommendations for banks include more tie-ups with property agents, greater peripheral benefits to attract borrowers and inclusion of a ‘refinancing calculator’ on their websites.